First to arrive : state and local responses to terrorism - Kayyem, Juliette N.; Pangi, Robyn L. (BCSIA studies in international security., 2003)
"These essays grew out of a series of disussions held by the Executive Session on Domestic Preparedness at Harvard University's Kennedy School of Government. Begun before the September 11 attacks and continuing after them, they offer a guide to U.S. domestic security in today's world."--Jacket